Peran Public Relations dalam Menghadapi Krisis (Studi pada Hotel Berbintang di Yogyakarta) - Nendyowati, Retnaningsih Eni; Birowo, Mario Antonius (Jurnal Kajian Ilmiah, 2023)
Star hotels in Yogyakarta are experiencing a crisis due to COVID-19. Consumer confidence in staying at hotels has decreased drastically because consumers have the perception that hotels have the opportunity to become a cluster of COVID-19 spreads. This perception is supported by news coverage in the mass media and viral videos showing violations of health protocols. Government regulations regarding social restrictions and conditions such as antigen and PCR testing have caused people to choose to stay at home as often as possible. Therefore, this study will discuss the strategies carried out by public relations in shaping the image of the hotels as a safe place during the pandemic and forming a public trust to return to activities in star hotels. This research uses situational crisis communication theory to analyze management, communication, and response strategies of crisis. It uses qualitative methods and case study approach. Data was collected through in-depth interviews with general managers, heads of departments, and public relations at star hotels in Yogyakarta. The findings in this study indicate that public relations use rebuilding strategy utilizing rhetoric of renewal. Public relations rebuild the image of hotel as safe place during the pandemic by presenting content in the form of implementing health protocols. The description about public relations’ work has been writing on result and discussion section.